Can a comparative capitalism approach explain fiscal policy activism?. Issue 3 (3rd July 2017) - Kalinowski, Thomas; Hlasny, Vladimir
ABSTRACT: This study investigates the implications of models of capitalism for the responsiveness of countries' fiscal policies during business cycles using new data for member countries of the Organization for Economic Cooperation and Development and China. We expand the literature by adding the category of East Asian nonliberal capitalism to the established distinction of liberal market economies and nonliberal coordinated market economies. These three differ substantially not just in their fiscal policies, but also in monetary policies, degree of financial market orientation, exchange rate regime, and labor market organization. As in previous studies, we find that governments of liberal economies adopt more countercyclical fiscal policies. Departing from existing studies, however, among the nonliberal models of capitalism, (East Asian) state-led models have more countercyclical fiscal policies than (European) coordinated market economies, perhaps as countercyclical as liberal economies, both historically and during the 2007–9 crisis. This is due to less independent central banks, managed float of exchange rates, and limited financial market orientation and financial openness in East Asia, which allow for more active fiscal policy. Among political factors, left-of-center governments, fractionalized party systems, and election years are associated weakly with countercyclical fiscal policy, as expected. Labor market coordination and welfare generosity have unclear roles in regard to fiscal policy, a topic for future research.